Dampak Kognitif, Afektif dan Sosial dari Pengalaman Situasi Krisis - Mufied Fauziah; Fiki Prayogi (Bulletin of Counseling and Psychotherapy, 2022)
Most people will try to find alternative solutions that can be done to solve problems or events that can cause stress. When internal resources and other external resources are unable to solve the problem, the individual will be trapped in a crisis situation. This study aims to examine the cognitive, emotional and social impacts that can be experienced by individuals with experiences facing crisis situations in their lives. The research uses a qualitative approach with the type of phenomenological research. The sample in this study were students of the Guidance and Counseling Study Program, Faculty of Teacher Training and Education, Ahmad Dahlan University as many as 56 students taken by purposive sampling (students who had experienced crisis situations). Data collection was carried out using questionnaires and interviews. The data were analyzed by collecting and describing all the phenomena that occurred as a result of the crisis experience experienced by the individual and grouped by type. The results of this study reaffirm that unresolved crisis conditions can have a long-term impact on cognitive, emotional and social aspects and have negative impacts. In the cognitive aspect, some of the stress reactions that arise are still often remembering events, negative self-image and difficulty concentrating. In the affective aspect, the stress reactions that arise include feelings of anxiety, fear, sadness, anger, anxiety, loss of hope and uncontrolled mood changes. On the social aspect, stress reactions that arise include withdrawing behavior from the social environment, difficulty interacting with other people and avoiding certain places or activities.